AB0595 Favourable Renal Outcome in AAV Nephritis: A CASE Series Reported from A Tertiary Referral Center. (10th June 2014) - Sarı, M.; Ince, B.; Ozluk, Y.; Erer, B.; Gul, A.; Inanc, M.; Ocal, L.; Kilicarslan, I.; Kamali, S.
Abstract : Background: A new histopathological classification was developed to predict renal outcome in AAV nephritis 1 . Objectives: We aimed to investigate the relationship between histopathological findings and renal outcome by using this new classification. Methods: Forty-three AAV patients (60% GPA, 40% MPA) diagnosed according to CHCC and followed-up between 2000-2013 and were included into the study. Demographic, clinical and treatment characteristics were recorded into a predefined protocol. Cyclophosphamide and pulse/high dose methylprednisolone was used in remission induction for at least 6 months in all patients. Renal biopsy specimens including ≥10 glomeruli at diagnosis were evaluated by two pathologists (IK, YO) by using new AAV nephritis histopathologic classification. e-GFR at 0, 6th, 12th, 24th, 60th months were calculated with MDRD formula. Mann Whitney U test was used to compare the e-GFR at 0, 6th, 12th, 24th and 60th months within histopathological subgroups. Correlation of the percentage of the normal glomeruli number and the difference between initial and each follow-up e-GFR values in subgroups were tested by Spearman analysis. Results: Demographic features of AAV cohort (51% women) were as follows: Mean age at diagnosis was 47, 5±14, 9 (17-75) (median 49) and total disease duration was 59±41 months (median 53). ANCA testing was positive in 93% (c-ANCA 67%, p-ANCA 27%, c-ANCA/anti-PR3%30, p-ANCA/anti-MPO %14). Kidney was the only involved organ in 25% of cohort. Ten (23%) patients had pulmonary-renal syndrome. Mean disease activity score (BVAS03) was 20±6 (0-38). Four patients died (1 acute renal failure, 1 malignancy, 2 sudden death). The AAV cohort was classified as focal (FS) (37%), crescentic (CS) (40%) and mixed (MS) (23%) subgroups by new classification. No patient was classified for sclerotic subgroup. Median e-GFR values for the histopathologic subgroups during the follow-up visits were shown in figure 1 . The focal subgroup demonstrated stable e-GFR values during the follow-up with the highest median e-GFR values in comparison to the other subgroups. Initial e-GFR<15 was found as 53% in the CS. e-GFR was found to be increased significantly between the initial and each follow-up visits in those patients. The MS had an increased e-GFR values, which was became significant 12th and 24th months visits, during the follow-up. Only CS showed a positive correlation between the percentage of the number of normal glomeruli and the e-GFR changes during the first 2 years, but it was not statistically significant. Conclusions: The focal category according to the new histopathological classification was found to have a better renal outcome in this small group of AAV nephritis cohort, as reported in the literature. Three-forth of the patients, who underwent hemodialysis at the time of diagnosis were in the CS. A significant increase of e-GFR was demonstrated with the standard immunosuppressive treatment in the active patients. Renal function showed a trend towards an increase in accordance with the percentage of the normal glomeruli in the CS. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4882